(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2023)
The Yuman communities of Baja California and California have taken comfort in the word Auka, greeting that these communities have, whose closest meaning would be let the light shine on you; so it has a spiritual and religious condition. From this term, there is a resistance movement against the homogenization and acculturation of these societies, in addition to being a symbol of union with members of cultures different. Auka is also an element to market various products from a cultural element alien to other inhabitants of the Californian region and thus be able to survive the neoliberal development of the region. This word has meanings of asking for help and of being in exile; The expression even shows that even on your own land you can be a stranger waiting for some illumination. It is necessary to recognize these forms of resistance and identity from language and its use to reach an applied intercultural thought, and in this way that society and the anthropologist not only generate empathy for the similarities, but also for the differences. The anthropological gaze cannot only remain within the formal socio spatial delimitations, it has to position itself within conceptual and practical frontiers.